An amino acid substitution in the Drosophila hopTum-l Jak kinase causes leukemia-like hematopoietic defects. - Luo, H.; Hanratty, W.P.; Dearolf, C.R. (The EMBO Journal, 1995)
Proteins of the Jak family of non-receptor kinases play important roles in mammalian hematopoietic signal transduction. They mediate the cellular response to a wide range of cytokines and growth factors. A dominant mutation in a Drosophila Jak kinase, hopscotchTumorous-lethal (hopTum-l), causes hematopoietic defects. Here we conduct a molecular analysis of hopTum-l. We demonstrate that the hopTum-l hematopoietic phenotype is caused by a single amino acid substitution of glycine to glutamic acid at residue 341. We generate a true revertant of the hopTum-l mutation, in which both the molecular lesion and the mutant hematopoietic phenotype revert back to wild type. We also examine the effects of the G341E substitution in transgenic flies. The results indicate that a mutant Jak kinase can cause leukemia-like abnormalities.